(untitled) - Juarez, Jon (Boston, 2005)
This kind of book can be used in conjunction with an instructor-led course too. However, if you cannot find a good course in your area, or cannot afford one, these books are the best for learning on your own.
Keywords: Database management,Databases; Computer programs,Access control